Towards Sustainable Success: The Role of Growth Mindset in Building Grit in Multi-Level Business Marketing Members - Ramadina, Fadillah Rizki; Azis, Abdul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Long-term success in a multi-level marketing business environment is a dream for members. But given the challenges and high failure rate in MLM business. Grit becomes an important factor for success. Growth mindset, the belief that abilities can be developed through dedication and hard work. Growth mindset is assumed to influence grit, which is a combination of passion and perseverance to achieve long-term goals. This study aims to examine the role of growth mindset in building grit in multi-level marketing business members. The data in this study were obtained through questionnaire answers to respondents. The sample in this study amounted to 135 respondents. Data analysis in this study used simple linear regression analysis. The results of this study indicate a positive effect of growth mindset on grit in mlm members. Growth mindset affects grit in all aspects, namely consistency of interest and perseverance of effort positively. This means that if there is an increase in growth in mindset, the higher the grit will be. The results of the study are expected to contribute to the development of training strategies and self-development for MLM members, so that they can increase their grit and achieve success in business. Kesuksesan jangka panjang pada lingkungan bisnis multi level marketing menjadi impian bagi member bisnis. Namun mengingat tantangan dan tingkat kegagalan yang tinggi dalam bisnis MLM. Grit menjadi faktor penting bagi keberhasilan. Growth mindset, yaitu keyakinan bahwa kemampuan dapat dikembangkan melalui dedikasi dan kerja keras. Growth mindset diasumsikan dapat mempengaruhi grit, yaitu kombinasi dari passion dan perseverance untuk mencapai tujuan jangka panjang. Penelitian ini bertujuan untuk mengkaji peran growth mindset dalam membangun grit pada member bisnis multi-level marketing. Data pada penelitian ini didapat melalui Jawaban kuesioner pada responden. Sampel pada penelitian ini berjumlah 135 responden. Analisa data pada penelitian ini menggunakan analisis regresi linear sederhana. Hasil pada penelitian ini menunjukkan adanya pengaruh positif growth mindset terhadap grit pada member mlm. Growth mindset mempengaruhi grit pada semua aspek yaitu konsistensi minat dan ketekunan usaha secara positif. Hal tersebut mengartikan apabila terjadi peningkatan pada growth mindset maka akan semakin tinggi grit yang dimiliki. Hasil penelitian diharapkan dapat memberikan kontribusi bagi pengembangan strategi pelatihan dan pengembangan diri bagi member MLM, sehingga dapat meningkatkan grit serta mencapai kesuksesan dalam bisnis.